2016
DOI: 10.1111/1346-8138.13622
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ixekizumab treatment for Japanese patients with moderate to severe plaque psoriasis, erythrodermic psoriasis and generalized pustular psoriasis: Results from a 52‐week, open‐label, phase 3 study (UNCOVER‐J)

Abstract: Psoriasis, a chronic, immune‐mediated skin disease characterized by red, scaly plaques, affects approximately 0.3% of the population in Japan. The aim of this open‐label study was to evaluate the long‐term efficacy and safety of ixekizumab, a humanized, anti‐interleukin‐17A monoclonal antibody, in Japanese patients with plaque psoriasis (n = 78, including 11 psoriatic arthritis), erythrodermic psoriasis (n = 8) and generalized pustular psoriasis (n = 5). Ixekizumab was administrated s.c. at baseline (week 0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
186
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(213 citation statements)
references
References 17 publications
11
186
1
5
Order By: Relevance
“…However, to reveal the role of biologics in the treatment of GPP from the perspective of EBM, RCT are needed to compare the efficacies of biologics and other treatment methods. However, at present, it is necessary to rely on the open‐label studies or on the accumulation of case reports because of the limited number of clinical cases and severity of disease in many cases.…”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to reveal the role of biologics in the treatment of GPP from the perspective of EBM, RCT are needed to compare the efficacies of biologics and other treatment methods. However, at present, it is necessary to rely on the open‐label studies or on the accumulation of case reports because of the limited number of clinical cases and severity of disease in many cases.…”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 99%
“…In 2016, another anti‐IL‐17 antibody, ixekizumab, and an anti‐IL‐17 receptor antibody, brodalumab, were approved for health insurance coverage in Japan for patients with psoriasis vulgaris, psoriatic arthritis, pustular psoriasis and psoriatic erythroderma. The efficacy and safety of ixekizumab and brodalumab including GPP patients in an open‐label trial have been reported . Some characteristic side‐effects of IL‐17 blockage have been reported including Candida albicans infection, exacerbation of Crohn's disease and neutropenia .…”
Section: Chapter V: Strength Of Recommendations and Comments For Eachmentioning
confidence: 99%
“…IL‐17 inhibitors directly suppress the IL‐17 pathway, which is related to psoriasis. Therefore, the rates of patients attaining at least 75% improvement from baseline in the Psoriasis Area and Severity Index (PASI)‐75 and PASI‐90 were extremely high in previous studies of other biologics, and the effect was expressed rapidly . Anti‐IL‐23p19 antibody formulation for clinical use is in the final stages of development, and it has also been reported to be very effective .…”
Section: Treatment Strategy For Psoriasis Based On Its Pathogenesismentioning
confidence: 99%
“…4). [19][20][21] In patients who received ADA 80 mg every other week, 17 required switching from other biologics to ADA (IFX, 12 cases; UST, four cases; IXE, one case). 3).…”
Section: Discussionmentioning
confidence: 99%